Effect of some insecticides and their compatibility with fungicides on the growth of Ascochyta rabiei causing chickpea blight - MAHENDRA PAL, RAM SINGH* and (Indian Phytopathology, 2002)
Five insecticides were evaluated alone or in combination with four fungicides for their antifungal activity against Ascochyta rabiei (Pass.) Labr. All insecticides proved inhibitory/fungistatic to fungal growth. Quinalphos and monocrotophos resulted in maximum growth inhibition at 30°C and pH 3.0. The inhibitory action of all the fungicides was significantly enhanced when used in combination with quinalphos and higher dose (72 µl a. i.m of monocrotophos. However, the efficacy of thiram and captafol was significantly reduced in combination with lower dose (36 µl a.i/l) of monocrotophos.